(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
The article examines integration methods that contribute to the enhancement of educational and methodological support in the credit-module system (CMS). It analyzes contemporary approaches to integrating educational technologies, interdisciplinary connections, and digital tools to improve learning effectiveness.